Dinamika profil hematologi dan rasio netrofil:limfosit monyet ekor panjang (Macaca fascicularis) pada pengaturan mikroklimat ruangan - Ridzki M.F. Binol; Agik Suprayogi; Huda S. Darusman (Institut Pertanian Bogor, 2010)
The aim of this study was to obtain the profile of physiological hematology (erythrocyte, PCV, Hb, MCV, MCH, MCHC, and leukocyte) and the profile of ratio between neutrophil and lymphocyte of long-tailed macaque (Macaca fascicularis) in different microclimate conditions due to the room's temperature and humidity setting. The symptom of stress was also observed in this study. The research used 10 male macaques aged of 4 until 5 years old which placed in room temperature and humidity of 29,00±1,95°C and 79,52±1,57% respectively 7 days for adaptation period. Further more, the room temperature and humidity were set into 25,79±1,16°C and 80,19±9,05°/o during 14 days for treatment period. For the last treatment, macaques were reconditioned in room temperature and humidity of 29,00±1,95°( and 79,52±1,57°/o during 14 days for post-treatment period. Blood samplings were collected through femoralis vein on last day of adaptation period, continued with treatment and post-treatment periods as the day 1, 4, 7, 14, and 28. The results showed that there were not significant difference by room temperature and humidity setting to hematology and neutrophil: lymphocyte ratio. It could be proven by all parameters score obtained were still in normal ranges compared to literatures. There was also no stress symptom based on neutrophil:lymphocyte ratio measurement. Condition with room temperature and humidity of 25,79±1,16°C dan 80,19±9,05% regarded as the most suitable condition for long-tailed macaque'slife.